Метод исследования высокочастотных колебаний при горении твердого топлива в камере сгорания - Золоторев, Николай Николаевич (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The development of hardware and software technologies has now greatly expanded the possibilities of determining the phenomena associated with the study of the operation of a rocket engine. During the operation of a solid propellant rocket engine, high-frequency oscillations can occur in the combustion chamber, which contribute to the development of vibrational or resonant combustion. The paper presents the results of developing a technique for studying acoustic conductivity depending on the length of the resonator (combustion chamber). Experimental studies were carried out on a double-ended combustion chamber equipped with a pressure relief receiver. Registration of high-frequency vibration signals was carried out using piezoelectric sensors connected to a digital oscilloscope with the results output to a PC. The ignition system with the help of electrocapsule ignition and ignition wire has been worked out. The dependence of the oscillation frequency and acoustic conductivity of the combustion surface on the resonator length is obtained.